Peran Digital Marketing dalam Meningkatkan Ekonomi Keluarga di Desa Gambiran - Sonia Puspita Sari; Dwi Wulandari; Dewi Komala Sari; Indah Apriliana Sari (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The UMKM sector is one of the main pillars of the foundation of the Indonesian economy. The digital world is predicted to be a determining point for all human activities, including the economy. In fact, there has been a strong desire from SMEs to adopt technology in marketing. However, there are problems faced by UMKM so that the use of this technology is not going well. As happened in Gambiran Village, namely the lack of use of digital marketing in UMKM. Apart from that, there are still many mothers in Gambiran Village who rely on the role of the head of the family as the main producer of the family economy. Not only that, the mothers in Gambiran Village also don't have the confidence to start a business. The method in this study was carried out by providing socialization regarding the importance of digital marketing. In carrying out these socialization activities several stages are needed, the first stage is activity planning, the second stage is the implementation of socialization activities and the last stage is activity evaluation. The socialization activities were carried out on Saturday, January 28 2023 at the Gambiran Village Hall. The purpose of holding this socialization is that it is hoped that the Gambiran Village PKK can recognize the potential to start a business using technology. In addition, the use of this technology is expected to be able to assist the marketing process in the business that will be carried out.